The role of defects in the persistent photoconductivity of BaSnO3 thin films. (24th February 2023) - Figueroa, C; Villafuerte, M; Straube, B; Ferreyra, J; Navarro, C; Runco Leal, V; Bridoux, G
Abstract: Time-dependent photoconductivity (PC) and PC spectra have been studied in oxygen deficient BaSnO3 thin films grown on different substrates. X-ray spectroscopy measurements show that the films have epitaxially grown on MgO and SrTiO3 substrates. While on MgO the films are nearly unstrained, on SrTiO3 the resulting film is compressive strained in the plane. Electrical conductivity in dark is increased in one order of magnitude for the films on SrTiO3 in comparison to the one on MgO. This leads to an increase of PC in the latter film in at least one order of magnitude. PC spectra show a direct gap with a value of E G = 3.9 eV for the film grown on MgO while on SrTiO3 E G = 3.36 eV. For both type of films, time-dependent PC curves show a persistent behavior after illumination is removed. These curves have been fitted employing an analytical procedure based on the frame of PC as a transmission phenomenon showing the relevant role of donor and acceptor defects as carrier traps and as a source of carriers. This model also suggests that in the BaSnO3 film on SrTiO3 more defects are created probably due to strain. This latter effect can also explain the different transition values obtained for both type of films.